Mean Amplitudes of Vibration of the Novel SbF₇²⁻ , BiF₇²⁻ and Dianions - Baran, Enrique José (1999)
Mean amplitudes of vibration of the recently reported pentagonal bipyramidal SbF₇²⁻ and BiF₇²⁻ dianions were calculated from vibrational spectroscopic data, in the temperature range between 0 and 1000 K. The results are briefly discussed and some comparisons with related species are made.